Decreased Angiopoietin Expression in Underactive Bladder Induced by Long-term Bladder Outlet Obstruction - Jae Heon Kim; Hee Jo Yang; Hong Jun Lee; Yun Seob Song (International Neurourology Journal, 2023)
Purpose Ischemia of the bladder can occur if neovascular formation cannot keep pace with hypoxia induced by chronic bladder outlet obstruction (BOO). The aim of this study was to examine changes in angiogenesis growth factor expression generated by chronic BOO in a rat model of underactive bladder. Methods Twenty female Sprague-Dawley rats aged 6 weeks were assigned to 4 groups (5 rats per group). Group 1 was the control. Group 2 underwent sham surgery. The rats in groups 3 and 4 underwent BOO and were followed up for 1 week and 8 weeks. Cystometry was carried out together with bladder tissue analysis at 1 week and 8 weeks postoperatively. Real-time polymerase chain reaction (PCR) assays were conducted to determine the expression level of angiogenesis-related growth factors. A hypoxia signaling pathway PCR array was additionally carried out. Results The group that underwent BOO for 8 weeks showed abnormal bladder function, with a diminished intercontraction interval, decreased maximal voiding pressure, and higher volume of residual urine (P<0.05). Hypoxia-inducible factor-1 alpha expression was elevated in this group. The expression levels of vascular endothelial growth factor (VEGF) and VEGF receptor messenger RNA (mRNA) in the BOO group were comparable to those in the control group. However, angiotensin/tie receptor mRNA expression levels increased at 1 week after BOO, but decreased at 8 weeks after BOO. In animals that underwent BOO, fewer blood vessels exhibited positive immunofluorescent staining for von Willebrand factor. Alterations were also seen in the hypoxia signaling pathway PCR array. Conclusions In a rat model of underactive bladder caused by surgical BOO, reduced angiopoietin expression was demonstrated. This observation might underlie visceral ischemia and fibrosis associated with the procedure. The findings of this study might offer an improved understanding of the disease processes underlying BOO and facilitate selection of the appropriate time to repair the organ in this condition.